Errores en la medición de la temperatura del aire en una caseta meteorológica tipo Stevenson - Castro León, Vilma (1983)
The temperature of the air inside a double louvered meteorological screen relative to the temperature of the air outside the screen was considered. differences of the order of ±O.6 °C were recorded, due apparently to lack of ventilation. Temperature gradients in the screen were also measured. On clear days temperature differences between the inside-outside walls of the screen reached 7°C.